Non-performing loans and macroeconomic indicators in Asian Pacific Region: a dynamic panel data analysis / Nur Najwa Ibrahim @ Hashim - Ibrahim @ Hashim, Nur Najwa (2013)
This paper uses dynamic panel data methods to examine the effect of macroeconomic indicators on the non-performing loans (NPLs) in the Asian Pacific Region. Applying yearly data for twelve (12) years from 2000 to 2011 for eighteen countries, the dependent variable in this study is non-performing loans (NPLs) while the interest rate (INT), inflation rate (INF), economic growth (GDP) and exchange rate (EXC) are the independent variable in this study. Other than that, this study was being tested using Pooled Ordinary Least Square (POLS), Random Effect (Breusch and Pagan Lagrangian Multiplier Test), Random Effect Generalized Lease Square Regression (GLS) and Fixed Effect (Hausman Fixed Test). The results suggest that interest rate, inflation rate are significant and having positive and negative relationship with NPLs. The others variable are not significant with NPLs.